Discontinuation and non‐publication of heart failure randomized controlled trials: a call to publish all trial results. (15th November 2020) - Khan, Muhammad Shahzeb; Shahid, Izza; Asad, Nava; Greene, Stephen J.; Khan, Safi U.; Doukky, Rami; Metra, Marco; Anker, Stefan D.; Filippatos, Gerasimos S.; Fonarow, Gregg C.; Butler, Javed
Abstract: Aims: Discontinuation or non‐publication of trials may hinder scientific progress and violates the commitment made to research participants. We sought to identify the prevalence of discontinuation and non‐publication of heart failure (HF) clinical trials. Methods and results: We conducted a cross‐sectional search of ClinicalTrials.gov to identify all completed and discontinued HF clinical trials. We limited our search to only include trials that were completed by 31 December 2017. Trials were investigated to identify reasons for discontinuation. Informative termination was defined as trial termination due to safety or efficacy concerns. Data pertaining to the trial phase, funding, intervention, enrolment, and trial completion date were extracted for each trial. A total of 572 trials were included. Of these, 21% ( n = 118) were discontinued before completion. Patient accrual was the most frequently cited reason ( n = 42; 36%) for trial discontinuation, followed by informative termination ( n = 16; 14%) and funding ( n = 14; 12%). Overall, 24 780 patients were enrolled in trials that were terminated. Of trials that were completed and not terminated, nearly one‐third ( n = 131/454; 29%) were not published. Seventy‐nine (24%) trials were published within 12 months, 192 (59%) within 24 months, and 252 (78%) trials within 36 months. Conclusions: Discontinuation and non‐publication of HF trials is common. This raises ethical concerns towards participants who volunteer for research and are exposed to potential risks, inconvenience, and discomfort without furthering scientific progress.